Facile approaches of polymeric face masks reuse and reinforcements for micro-aerosol droplets and viruses filtration: A review - Wibisono, Y. (MDPI AG, 2020)
Since the widespread of severe acute respiratory syndrome of coronavirus 2 (SARS-CoV-2) disease, the utilization of face masks has become omnipresent all over the world. Face masks are believed to contribute to an adequate protection against respiratory infections spread through micro-droplets among the infected person to non-infected others. However, due to the very high demands of face masks, especially the N95-type mask typically worn by medical workers, the public faces a shortage of face masks. Many papers have been published recently that focus on developing new and facile techniques to reuse and reinforce commercially available face masks. For instance, the N95 mask uses a polymer-based (membrane) filter inside, and the filter membrane can be replaced if needed. Another polymer sputtering technique by using a simple cotton candy machine could provide a cheap and robust solution for face mask fabrication. This review discuss the novel approaches of face mask reuse and reinforcement specifically by using membrane-based technology. Tuning the polymeric properties of face masks to enhance filterability and virus inactivity is crucial for future investigation. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.